Comparison of Real Response Modification Factors and Performance of SMRFS Structure with OMRFS Structure Using Pushover Method - Friska Damayanti; Resmi Bestari Muin (Universitas Mercu Buana, 2023)
The value of the earthquake response modification factor ( ) affects the results of the story drift in the SMRSF structure, where the smaller the -value, the larger the deviation and the need for longitudinal reinforcement will be more and more. For structures that do not comply with the SMRSF provisions, in some locations the need for reinforcement is less than that of structures that use the SMRSF provisions. The performance of a structure can be analyzed using the pushover method. The research was conducted with a 4-story and 8-story configuration, with soft soil and medium soil conditions and using SMRSF and OMRSF. From research analysis results, the cross-sectional dimensions of the columns and beams of the ordinary moment building structure system with soft soil type are the largest cross-sectional dimensions compared to the others. Under the provisions of ATC-40, the structure is included in the Damage Control (DC) category level, which means the building is still able to withstand the force of the earthquake, and the risk of fatalities humans are very small. The real -value of the structure with SMRSF is not much different from the in the provisions of SNI 1726:2019.